An Overview of Managements in Meningiomas - Zhao, Lianhua; Zhao, Wei; Hou, Yanwei; Wen, Cuixia; Wang, Jing; Wu, Pei; Guo, Zaiyu (Frontiers in Oncology, 2020)
Meningioma is the most frequent primary tumor of the central nervous system. Important advances have been achieved in the treatment of meningioma in recent decades. Although most meningiomas are benign and have a good prognosis after surgery, clinicians often face challenges when the morphology of the tumor is complicated or the tumor is close to vital brain structures. At present, the longstanding treatment strategies of meningioma are mainly surgery and radiotherapy. The effectiveness of systemic therapy, such as chemotherapy or targeted therapy, has not been confirmed by big data series, and some clinical trials are still in progress. In this review, we summarize current treatment strategies and future research directions for meningiomas.